Importing the Human Factor into Safe Human–Robot Interaction Function Using the Bond Graph Method. Issue 5 (12th May 2021) - Cheng, Po-Jen; Ting, Hsiang-Yuan; Huang, Han-Pang
SUMMARY: The variable stiffness actuator (VSA) is helpful to realize the post-collision safety strategies for safe human–robot interaction. 1 The stiffness of the robot will be reduced to protect the user from injury when the collision between the robot and human occurs. However, The VSA has a mechanism limit constraint that can cause harm to users even if the stiffness is minimized. Accordingly, in this article, a concept combining danger index and robust fault detection and isolation is presented and applied to active–passive variable stiffness elastic actuator (APVSEA). APVSEA can actively change joint stiffness with the change of danger index. Experimental results show that this concept can effectively confirm the fault mode and provide additional protection measures to ensure the safety of users when the joint stiffness has been adjusted to the minimum.